A New Suture Technique Avoids Rib Fractures and Intercostal Nerve Trauma in Thoracotomy - Huang, Biaotong (The Thoracic and Cardiovascular Surgeon, 2014)
This article describes an alternative suture technique for thoracotomy incisions. A modified mattress suture technique is used to fix the intercostal muscles. The described technique can prevent rib fractures and reduce the incidence of intercostal nerve injury. Also, this technique is easy to perform and is effective.
Keywords: thoracotomy; suture techniques; mattress suture; postoperative pain